Effect of Seed Maturity on Seed Quality, Field Emergence, Growth and Yield of KUP 24D-421 Large-seeded Peanut - Juangjun Duangpatra; Somtawin Wongmajaroensin (Agriculture and Natural Resources, 1993)
Non-uniformity in maturity of peanut seed affects quality of seed and the products derived from it. The study on the effect of seed maturity on quality of seeds to be used for planting, growth and yield was studied in KUP24D-421 large¬seeded peanut line. Dry and sound mature peanut pods were hand shelled and divided into three different maturity groups on the basis of internal pericarp color. Seeds of each maturity group were further categoried into three different seed coat wrinkle levels. Seed moisture content, germination and vigor as determined by germination index, seedling dry weight and accelearted aging test were carried out in the laboratory. Seeds from these nine groups were also planted on ridges spaced 50 cm. apart, 20 cm. between hill with two seeds per hill. Field emergences were determined at 7, 14 and 21 days after planting. Plant height and dry matter were recorded at 30 to 120 days after planting. harvesting was done at 140 days from which pod and seed yield were recorded. Results indicated that seed maturity and seed coat wrinkle level did not affect peanut seed germination and seed vigor. The intermediate maturity group seeds were highest in field emergence percentage. Fully mature and non-wrinkle seeds showed the best growth and development at ealy growth stages but not at the later stages. Seed maturity and seed coat wrinkleness did not affect pod yield, seed yield, shelling percentage and seed weight. This revealed that the immature and wrinkle seeds can be used for planting whereas the fully mature and non-wrinkle ones can bd sorted for peanut products.